2021
DOI: 10.3390/v13091846
|View full text |Cite
|
Sign up to set email alerts
|

Dangerous Liaisons: Long-Term Replication with an Extrachromosomal HPV Genome

Abstract: Papillomaviruses cause persistent, and usually self-limiting, infections in the mucosal and cutaneous surfaces of the host epithelium. However, in some cases, infection with an oncogenic HPV can lead to cancer. The viral genome is a small, double-stranded circular DNA molecule that is assembled into nucleosomes at all stages of infection. The viral minichromosome replicates at a low copy number in the nucleus of persistently infected cells using the cellular replication machinery. When the infected cells diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 126 publications
(181 reference statements)
1
28
0
Order By: Relevance
“…The HPV E2 protein is the master regulator of the virus life cycle, with main roles involving the control of gene transcription and viral genome replication (McBride, 2013). E2 role in transcription is well characterized, it functions primarily by recruiting cellular factors to the viral genomes, which activate or repress transcriptional processes upon specific binding to the viral genome in a dose-dependent manner (McBride, 2013; Warburton et al, 2021). Additionally, E2 acts as a loading factor for the viral helicase E1 at the HPV origin of replication and in late stages of replication has crucial roles in genome maintenance and partition (Warburton et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The HPV E2 protein is the master regulator of the virus life cycle, with main roles involving the control of gene transcription and viral genome replication (McBride, 2013). E2 role in transcription is well characterized, it functions primarily by recruiting cellular factors to the viral genomes, which activate or repress transcriptional processes upon specific binding to the viral genome in a dose-dependent manner (McBride, 2013; Warburton et al, 2021). Additionally, E2 acts as a loading factor for the viral helicase E1 at the HPV origin of replication and in late stages of replication has crucial roles in genome maintenance and partition (Warburton et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…E2 role in transcription is well characterized, it functions primarily by recruiting cellular factors to the viral genomes, which activate or repress transcriptional processes upon specific binding to the viral genome in a dose-dependent manner (McBride, 2013; Warburton et al, 2021). Additionally, E2 acts as a loading factor for the viral helicase E1 at the HPV origin of replication and in late stages of replication has crucial roles in genome maintenance and partition (Warburton et al, 2021). The E2 proteins are around 400 amino acid polypeptides consisting of an N-terminal transactivation domain (ca.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, regulatory viral factors such as the E8^E2 repressor have been shown to regulate genome copy number (5,6). During maintenance, genome is replicated via the bi-directional mode (1,7,8). Several reports have suggested that differentiation-induced genome amplification utilizes a rolling circle mechanism based mainly on data derived from the analysis of two-dimensional gel electrophoresis (8)(9)(10)(11).…”
Section: Importance Introductionmentioning
confidence: 99%